ANALISIS SPASIAL DALAM KLASIFIKASI LAHAN KRITIS DI KAWASAN SUB-DAS LANGGE GORONTALO - Anasiru, Rahmat Hanif (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Watershed (DAS) is a complex ecosystem, where land quality is largely determined by land use activities. This illustrates the importance of analytical procedure, especially where the context in which the spatial pattern of land use in the future can be designed based on the risk of degradation in large areas. Data and information are necessary to be used as reference in designing a planning scheme related to land use. Geographic Information Systems (GIS) is a system that has the ability to analyze problems and their spatial and non-spatial combinations (queries) in order to provide solutions to spatial problems. Sustainable farming is an integral part of sustainable development, a farming system which preserves water resources, land resources, and plant resources in acceptable and suitable ways economically, socially, and environmentally. The research aimed to identify and classify critical land by spatial analysis. Based on identification of land, there were 12 individual units in the study area. Based on the spatial analysis, critical land classification was divided into not critical area of 1,818 ha (28.7.%), Potentially Critical 2,596 ha (41.06%), Moderately critical 1,631 ha (25.08%), Critical 226 ha (3.57 %). Most of the land in sub-basin Langge was a hilly area of 1180.6 ha (63.8%) with a slope of 12-25%; 25-40% and above 40%. Alternative farm management in this area was a conservation farm by mechanical conservation techniques (terraces) or vegetative with cultivation techniques hallway, living fences, grass strips and agroforestry.